2022
DOI: 10.3389/fimmu.2022.952398
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism and glycosylation link the gut microbiota to autoimmune diseases

Abstract: Carbohydrates serve as important energy sources and structural substances for human body as well as for gut microbes. As evidenced by the advances in immunometabolism, glucose metabolism and adenosine triphosphate (ATP) generation are deeply involved in immune cell activation, proliferation, and signaling transduction as well as trafficking and effector functions, thus contributing to immune response programming and assisting in host adaption to microenvironment changes. Increased glucose uptake, aberrant expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 197 publications
0
6
0
Order By: Relevance
“…5E). This increase was associated with increased cytokine production, likely a direct impact of TGF-β signaling cascades (50,51). For the mito stress test, oxygen consumption rate (OCR) was used to determine oxidative phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…5E). This increase was associated with increased cytokine production, likely a direct impact of TGF-β signaling cascades (50,51). For the mito stress test, oxygen consumption rate (OCR) was used to determine oxidative phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we have shown the disease-specific nature of the T-antigen, providing evidence that it could be expressed in both pre-cancerous lesions as well as cancer, being associated with the presence of metastases. The almost exclusive expression of the T-antigen on secretions and very rare detection in epithelial cells suggest possible remodeling of the mucus layer glycocalyx by the microbiome with a potential impact on disease, as suggested by different reports [25,26]. LGD and HGD and cancer (magnification: 400×).…”
Section: T-antigen In Colorectal Tissuesmentioning
confidence: 90%
“…A series of studies have reported that dysregulation of these enzyme activities can lead to imbalances in cellular redox status and impact various metabolic processes, such as glucose and lipid metabolism, as well as carbohydrate metabolism. These disruptions have been implicated in metabolic diseases such as diabetes, obesity, and cardiovascular diseases [ 32 34 ]. For example, Otaki et al firstly reported that plasma xanthine oxidoreductase activity with severity and clinical outcome in patients with chronic heart failure [ 35 ].…”
Section: Rational Design Strategiesmentioning
confidence: 99%